2017
DOI: 10.1177/0033294117692808
|View full text |Cite
|
Sign up to set email alerts
|

Adult Chinese as a Second Language Learners' Willingness to Communicate in Chinese: Effects of Cultural, Affective, and Linguistic Variables

Abstract: The present research explored the effects of cultural, affective, and linguistic variables on adult Chinese as a second language learners' willingness to communicate in Chinese. One hundred and sixty-two Chinese as a second language learners from a Chinese university answered the Willingness to Communicate in Chinese Scale, the Intercultural Sensitivity Scale, Chinese Speaking Anxiety Scale, Chinese Learning Motivation Scale, Use of Chinese Profile, as well as the Background Questionnaire. The major findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…The analyses also revealed that the participants were generally (fairly) sensitive, confident, attentive and enjoyable in intercultural interactions and respected cultural differences when communicating with people in the Chinese culture, consistent with the findings in many existing studies (Anderson et al, 2006, Chen & Starosta, 2000Christmas & Barker, 2014;Liu, 2017Liu, , 2018bLiu & Liu, 2015;Lukesová, 2015;Martinsen, 2011;Sarwari & Wahab, 2017;Straffon, 2003;Tabatadze & Gorgadze, 2014). Meanwhile, the participants reported to be (highly) willing to communicate with others in Chinese, as found in Liu (2017Liu ( , 2018b and Yousef, Jamil & Razak (2013).…”
Section: Discussionsupporting
confidence: 86%
“…The analyses also revealed that the participants were generally (fairly) sensitive, confident, attentive and enjoyable in intercultural interactions and respected cultural differences when communicating with people in the Chinese culture, consistent with the findings in many existing studies (Anderson et al, 2006, Chen & Starosta, 2000Christmas & Barker, 2014;Liu, 2017Liu, , 2018bLiu & Liu, 2015;Lukesová, 2015;Martinsen, 2011;Sarwari & Wahab, 2017;Straffon, 2003;Tabatadze & Gorgadze, 2014). Meanwhile, the participants reported to be (highly) willing to communicate with others in Chinese, as found in Liu (2017Liu ( , 2018b and Yousef, Jamil & Razak (2013).…”
Section: Discussionsupporting
confidence: 86%
“…To explore the relationship between motivation for learning German and test performance, correlation analyses were run between the MLGQ scales and German test scores (see Table 2). The results showed that MGLL3 was significantly positively correlated with in-China learners' German test performance, and that the MLGQ, MLGQ1 and MLGQ2 were significantly positively related to SA learners' German test performance, consistent with that in other studies in SA contexts (Hernández, 2010;Hsieh, 2009;Liu, 2017b;Liu & Li, 2018), with a medium effect size. This means that the more motivated in-China students were to study German for miscellaneous purposes, the better they performed in German, and that the more instrumentally and/or integratively motivated SA students were to study German, the better they performed in German.…”
Section: Relationship Between Motivation For Learning German and Testsupporting
confidence: 87%
“…A generally similar pattern is observed in motivation studies in SA contexts, which has become an issue of interest in recent decades (Allen, 2010;Hernández, 2010;Hsieh, 2009;Liu, 2017aLiu, , 2017bMeredith, 2010 Hsieh's (2009) interview of two Taiwanese students studying in an American university indicated that the SA context had a great impact on the development of the participants' L2 motivational self system.…”
Section: Literature Reviewsupporting
confidence: 54%
See 2 more Smart Citations